Pemilihan Guru Terbaik, MPE, con Implementasi Metode Perbandingan Eksponensial (MPE) dalam Pemilihan Guru Terbaik di SMK XYZ - Wawan Setiawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The selection of the best Teachers on an ongoing basis is very important to determine active and accomplished teachers, as well as for evaluation materials and improving the quality of teachers. In the selection of the best teachers in SMK XYZ still manually and do not use standard reference criteria, resulting in a standard reference in providing an unclear assessment. In addition, in the absence of a standard ranking method or calculation the results are inconsistent. To make judgments that are consistent and objective, they must use reference criteria and methods for standard alternative ranking. Researchers in data collection through observation, interviews, documentation, literature studies and questionnaires. Researchers use the Exponential Comparison Method (MPE) for alternative calculation or ranking algorithms. Based on the results of the measurement of the level of Accuracy with the confusion metrix technique on the selection of the best teacher, a level of accuracy of 100% is obtained and based on the results of testing of the system that has been created using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, a value of 91.76% is obtained. , so that the system that has been built is feasible to use. The system created can support speeding up in making decisions, can reduce human error and be objective with reference to criteria and standard weights.